Incarceration, Liberation, Imagination - Figueroa, Saul
Incarceration, Liberation, Imagination by local artist Saul Figueroa features colorful, detailed mixed media artwork. The exhibit tells a compelling story of gang violence, prison life, and ultimately a story of faith and second chances. Incarceration, Liberation, Imagination provides CSUSM students and community an unflinching and intimate look into one man's perseverance through poverty, crime, and imprisonment.